Estimation of Lost Man Days among the Viral Hepatitis Patients Attended at a Tertiary Level Hospital in Bangladesh - Haque, Md Anwarul; Rahman, Ashiqur; Akter, Mst Ralifa (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Viral hepatitis can cause a range of health problems and can be fatal. It is also prevalent in Bangladesh Armed Forces personnel and causing significant number of loss of man days. Objective: To assess the total loss of man days due to viral hepatitis of army personnel admitted/treated in hospital. Methods: This cross sectional study was conducted at Combined Military Hospital (CMH), Dhaka among military persons. Total 103 hepatitis patients were selected by simple random sampling from June to November 2014. Data were collected by semi-structured questionnaire and analyzed by using ‘Statistical Package for Social Science (SPSS) version -19. Results: The age range was between 20 to 43 years and mean age was 33.2 ± 5.8 years. Most of them suffered from hepatitis B (68.9%). Considering the rank structure, majority (51.4%)were Non Commissioned Officers (NCOs) and stayed in sainik line (46.6%). Due to reporting at Out Patient Department (OPD), 76.7% got 1-7 days sick rest and 73.8% have lost 1-7 man-days. Mean total man days lost was 55 ± 36 days. Mean admission days at hospital were 17 ± 13.7 days and the highest percentage was NCO (47.1%) followed by Sainik (39.7%). Total admission days of Sainik was not significantly association with admission days of NCO. But significant association was found within losing total man days between these two groups (χ2 = 4.88, p < .05). Conclusion: The results confirm the significant loss of man days due to viral hepatitis infection in Armed Forces Personnel which should be considered as a public health problem. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 30-33